E-SUPPLY CHAIN MANAGEMENT PADA TOKO ROTI MENGGUNAKAN ODOO 11.0 - Dwi Putra Githa; I Made Sunia Raharja (SINTECH (Science and Information Technology) Journal, 2021)
The rapid development of technology has an impact on the competition in the business world. A company needs technology to be able to make efficiency and make innovations in order to maintain market share or to gain new market share. A company must make efficiency in all fields in order to increase competitiveness. A bakery is a manufacturing company that runs its business by making and selling bread. Electronic Supply Chain Management can be a solution for managing business processes related to bakery activities. Electronic Supply Chain Management (e-SCM) is the efficient and effective coordination of all supply activities of an organization from its suppliers and partners to its customers using technology support. E-SCM Bakery has been successfully built through the stages of data collection, data analysis, system business process design and system development using Odoo 11.0. Based on black box testing, all functionality of the system has been running as expected.